2019
DOI: 10.35940/ijrte.d5119.118419
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic Properties of Mixing Empty Fruit Bunch and Oil Palm Frond Natural Fibres

Abstract: Natural fibre is being studied and used as sound absorber for its promising acoustic properties. For instance, Germany have commercial plants that are producing sound absorbers from natural fibre. Natural fibre is eco-friendly and has no effect on human health. Besides that, the production cost of natural fibre is cheaper than synthetic fibre. This research reported the thickness effects on acoustic properties in different ratios of natural fibres of empty fruit bunch (EFB) and oil palm frond (OPF). Four diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Untreated Jute fibers showed an increasing trend of SAC from 0.38 to 0.95 with increasing in fiber length (5 mm to 20 mm) [11]. In addition, according to R. Mageswaran, et al, [12], a combination of EFB and OPF showed promising SAC value from 0.81-0.98 with a frequency range of 4000 -6400 Hz [12].…”
Section: Introductionmentioning
confidence: 88%
“…Untreated Jute fibers showed an increasing trend of SAC from 0.38 to 0.95 with increasing in fiber length (5 mm to 20 mm) [11]. In addition, according to R. Mageswaran, et al, [12], a combination of EFB and OPF showed promising SAC value from 0.81-0.98 with a frequency range of 4000 -6400 Hz [12].…”
Section: Introductionmentioning
confidence: 88%
“…1 to Fig. 7 show the dry LDF fabrication process, which involved chipping, refining, glue bending, mat-forming, pre-press, hot press, and cool-down process [8,17]. The density used in this research is 120 kg/m 3 .…”
Section: Methodsmentioning
confidence: 99%
“…They are renewable, biodegradable and most important of all, it is safe and healthy to humans and surrounding [8]. Some of the natural fibre that has been tested for their acoustic properties are kenaf [9], sugar palm [10], coconut [11], kapok [12], bamboo [13], OPF [14], OPT [15], etc.…”
Section: Introductionmentioning
confidence: 99%
“…According to a study conducted by R. Mageswaran et al, the fibreboard made with a combination of an empty fruit bunch and oil palm fronds exhibited good acoustic characteristics [9]. The study conducted by David J. Oldham et al revealed that natural fibres with small diameters are proved to be the best sound absorbers.…”
Section: Introductionmentioning
confidence: 99%